Combined spontaneous symmetry-breaking and symmetry-protected topological order from cluster charge interactions - Chen Peng; Rong-Qiang He; Yuan-Yao He; Zhong-Yi Lu (Physical Review Research, 2020)
The study of symmetry-protected topological states in the presence of electron correlations has recently aroused great interest as rich and exotic phenomena can emerge. Here we report a concrete example by employing a large-scale unbiased quantum Monte Carlo study of the Kane-Mele model with cluster charge interactions. The ground-state phase diagram for the model at half filling is established. Our simulation identifies the coexistence of a symmetry-protected topological order with a symmetry-breaking Kekulé valence bond order and shows that the spontaneous symmetry breaking is accompanied by an interaction-driven topological phase transition (TPT). This TPT features the appearance of zeros of a single-particle Green's function and gap closing in a spin channel rather than a single-particle excitation spectrum and thus has no mean-field correspondence.